Macrofossil evidence of alder (Alnus sp.) in Britain early in the Late Glacial Interstadial: implications for the northern cryptic refugia debate. (26th October 2020) - Young, D. S.; Green, C. P.; Batchelor, C. R.; Austin, P.; Elias, S. A.; Athersuch, J.; Lincoln, P.
ABSTRACT: Wood macrofossil remains of alder and willow/poplar have been recovered from a sediment sequence in the valley of the Turker Beck in the Vale of Mowbray, North Yorkshire. These remains have yielded radiocarbon dates early in the Devensian Late Glacial (14.7–14k cal a bp ), equivalent to the early part of the Greenland Interstadial (GI‐1e) of the GRIP ice‐core record. These are the earliest dates recorded for the presence of alder in the Late Glacial in the British Isles. Associated biological remains have provided a palaeoenvironmental record for this early part of the Greenland Interstadial, generally indicative of open environments dominated by herbaceous taxa on both the wetland and dryland surfaces. However, stands of alder, birch and willow woodland were also present, and indicate the possibility that such tree species survived in cryptic refugia in Britain as elsewhere in northern Europe during the Last Glacial Maximum. The absence of alder pollen at Turker Beck, in a sequence in which its macrofossil remains are relatively abundant, lends support to the view that pollen can be a poor indicator of the presence of tree species in Late Glacial sequences in northern and western Europe.